Building sustainable public transport in Malaysia - Ong, Yoon Yee; Aziz, Zulkufli (2012)
The paper evaluates Malaysian public transport in term of sustainability which is discussed within three frameworks: environmental, economic and social for improving the quality of public transport services, and attracting more passengers while increasing productivity, reducing costs, and providing environment friendly public transport service in future. The study aims to evaluate usage level of Malaysia’s public transport.The methodology of the study uses qualitative comparative analysis. As a result of this research, recommendations are made to promote sustainable public transport in Malaysia.The finding indicates that usage level of public transport is low and high ownership in private vehicle and thus calls for improvement.